Substance Use, Highly Active Antiretroviral Therapy, and Liver Enzymes: Evidence From a Cross-Sectional Study of HIV-Infected Adult Patients Without Comorbidities on HAART in the University of Port Harcourt Teaching Hospital - Anyanwu, Chinwe F.; JohnBull, Tamuno-Olobo; Usman, Ibe M.; Aigbogun, Eric O.; Ochai, Joy; Qasem, Ahmed H.; Alkhayyat, Shadi S.; Alexiou, Athanasios; Batiha, Gaber El-Saber (Frontiers in Reproductive Health, 2021)
This study applied a structural equation modeling (SEM) to evaluate the role of substance use (alcohol, smoking, and trado-medicine use) to changes in the liver enzymes (AST, ALT, and ALP) levels in HIV-infected adult patients on a highly active antiretroviral treatment (HAART) for not <1 year. The study was a cross-sectional, part of a randomized comparative trial (Ref: UPH/CEREMAD/REC/19), involving 129 (46 males and 83 females) HIV-infected adult patients. Liver enzyme levels were determined from analyzed blood samples using the Clinical Chemistry Analyser (VS10) manufactured by Vitro Scient, while the study determined substance use using a reliable (Cronbach alpha = 0.805) rapid-exploratory survey questionnaire. Liver enzyme values were further categorized into: normal or abnormal using normal reference ranges (ALT = 7–55 U/L, AST = 8–48 U/L, and ALP = 40–129 U/L). STATGRAPHICS V16.1.11 (StatPoint Tech., Inc.) and SPSS (IBM® Amos V21.0.0, USA) were used to analyze the data. Among the HIV-HAART patients, 27.9% were alcohol users, 20.9% smokers, and 20.1% trado-medicine users. In addition, ALP (71.3%) abnormality was higher than ALT (34.9%) and AST (28.7%). The result from the SEM provided only a partial support for our hypotheses of direct substance use effects on the liver enzyme levels and abnormalities; with a direct association of alcohol with an elevated AST (b = 0.170, p = 0.05) and smoking with a higher AST (b = 0.484, p < 0.01) and ALT (b = 0.423, p < 0.01) values. Trado-medicine use was not directly associated with enzyme elevation and abnormality. In conclusion, ALP abnormality was the most common, and there is a close association between an elevated ALT and AST, with or without an elevated ALP. The study found that HIV-HAART patients who drink or smoke will have at least one or more abnormal transaminases. The possible explanation to the increased risk among HIV-HAART patients could be associated with the metabolic pressures and supra-additive effects on the livers.